Biochemical Markers of Oxidative Stress in Intrauterine Growth Restriction (IUGR) - Iram Shahzadi, Rafia Javed, Shaheen Khan Bahadar, Safoora Anjum, Muzamil Liaqat Ali, Nadeem Abbas (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Intrauterine Growth Restriction (IUGR) is a significant obstetric complication characterized by suboptimal fetal growth, often due to placental insufficiency. Emerging evidence suggests that oxidative stress plays a pivotal role in the pathophysiology of IUGR. This study aims to evaluate the levels of various oxidative stress biomarkers in neonates diagnosed with IUGR compared to appropriate for gestational age (AGA) controls. The objective is to identify potential biomarkers that could serve as early indicators of IUGR and provide insights into its underlying mechanisms.